2016
DOI: 10.1093/ndt/gfw107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of renal artery revascularization upon cardiac structure and function in atherosclerotic renal artery stenosis: cardiac magnetic resonance sub-study of the ASTRAL trial

Abstract: Ritchie, J. et al. (2016) Effect of renal artery revascularization upon cardiac structure and function in atherosclerotic renal artery stenosis: cardiac magnetic resonance sub-study of the ASTRAL trial. Nephrology Dialysis Transplantation, (doi:10.1093/ndt/gfw107) This is the author's final accepted version.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/119879/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The cardiac magnetic resonance sub-study of the ASTRAL (Angioplasty and Stenting for Renal Artery Lesions) trial reported no benefits from renal artery stenting on LVM, compared with medical therapy. 34 However, according to the most updated meta-analysis of echocardiographic studies including 360 patients, 35 renal artery revascularization had a beneficial effect on LV structure. In the present study, ARAD patients without HF showed a significant decrease in LVMI after renal artery stenting whereas ARAD patients overall or ARAD patients with HF did not.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiac magnetic resonance sub-study of the ASTRAL (Angioplasty and Stenting for Renal Artery Lesions) trial reported no benefits from renal artery stenting on LVM, compared with medical therapy. 34 However, according to the most updated meta-analysis of echocardiographic studies including 360 patients, 35 renal artery revascularization had a beneficial effect on LV structure. In the present study, ARAD patients without HF showed a significant decrease in LVMI after renal artery stenting whereas ARAD patients overall or ARAD patients with HF did not.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac magnetic resonance was performed at recruitment and before revascularization in the intervention group ( n = 22) and compared with repeat CMR after 12 months. Over this period, there was improvement in left ventricular structural parameters in both arms, possibly due to the effect of modern cardioprotective therapy, but there was no significant difference between the two treatment arms [ 67 ]. These results echo those of a previous Italian study which investigated the effect of revascularization on left ventricular mass index (LVMI) using serial echocardiography in 84 patients with both ARVD and coronary artery disease over the same period.…”
Section: Management Of Atherosclerotic Renovascular Diseasementioning
confidence: 99%
“…While neither the large randomized controlled trials [1,2] nor subsequent subgroup analysis [3] have shown any benefit with respect to renal function or blood pressure for Percutaneous Transluminal Angioplasty (PTA) over medical therapy in patients with RAS, PTA continues to be advocated by guidelines Citation: Diskin CJ, Dansby LM, Carter TB, Radcliff L, Diskin CD. Long-term harm associated with renal artery stents in a temporally distant time after the renal function is Gone.…”
Section: Introductionmentioning
confidence: 99%